Feasibility Study Of Investment Clean Water Installation System In Distric Ermera Sub-Distric Gleno, Timor Leste - Ronny Durrotun Nasihien; Joanina M. N. da Silva (Journal of World Conference (JWC), 2020)
Increase of population count in every time, then the need of the for clean water is the also enhancment, to solve the problem is the needed of an installation system cleane water is the worthy. Feasibility study is an activity do for know about worthy or not worthy of the an project that the seen of various aspects such as financial aspect and social economic aspect before that project implemented. The purpose of this activity to the know investation feasibility of installation clean water in the gleno city and to discover effect of investation feasibility to the give revenue. on the investment phase the feasibility study of the clean water installasion system that there in the ermera distric, sub-distric gleno timor leste are using Net present value (NPV), Internal rate of rentrum (IRR), and Benefit Cost Ratio (IRC) whereas to find out the effec of investment feasibility to the revenue that give seen from fund the region revenue is abaout 20% and reserve fund general is about 15% from the results of the calculation of financial aspects that is obtained NPV>0 around Rp. 235.667.254 > 0, BCR > 1 around 1.421 > 1, IRR > 1,50% around 2.75% > 1,50 whereas the for aspects social economic that consist of the fund developmental regional and general fund reserve around Rp 47.133451 dan Rp 35.350.088